2008
DOI: 10.1128/aac.00323-08
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibilities of Invasive Isolates of Candida Species: Rapid Increase in Rates of Fluconazole Susceptible-Dose Dependent Candida glabrata Isolates

Abstract: Voriconazole, posaconazole, caspofungin, micafungin, and anidulafungin demonstrated potent in vitro activities against 286 invasive Candida isolates. Analysis of the fluconazole susceptibilities of 204 bloodstream Candida glabrata isolates revealed a rapid shift from susceptible (64% in 1999 to 2001 to 19% in 2007) to susceptible-dose dependent (27% in 1999 to 2001 and 75% in 2007).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 25 publications
3
12
2
Order By: Relevance
“…First, fluconazole retained potent in vitro activities (Ͼ99%) against C. albicans and C. parapsilosis, despite the persistently high rate of fluconazole consumption during the study period (62.9 defined daily doses [DDD]/1,000 inpatients in 2009 and 67.7 in 2010) (22). This observation supports the results of several previous studies in Taiwan and in other countries which showed that the susceptibility of Candida blood isolates to fluconazole has stabilized and, in some countries, increased even though the overall use of fluconazole has increased (22)(23)(24).…”
Section: Discussionsupporting
confidence: 81%
“…First, fluconazole retained potent in vitro activities (Ͼ99%) against C. albicans and C. parapsilosis, despite the persistently high rate of fluconazole consumption during the study period (62.9 defined daily doses [DDD]/1,000 inpatients in 2009 and 67.7 in 2010) (22). This observation supports the results of several previous studies in Taiwan and in other countries which showed that the susceptibility of Candida blood isolates to fluconazole has stabilized and, in some countries, increased even though the overall use of fluconazole has increased (22)(23)(24).…”
Section: Discussionsupporting
confidence: 81%
“…In fact, all the isolates were susceptible except for C. lusitaniae. The level of fluconazole resistance among the isolates tested was relatively low, similar to that found in other studies (Pfaller et al, 2005;OstroskyZeichner et al, 2003;Ruan et al, 2008). Only a few isolates of C. albicans (two), C. parapsilosis (two), C. tropicalis (one) and C. glabrata (one) were resistant to fluconazole and all of these isolates showed cross-resistance to itraconazole.…”
Section: Discussionsupporting
confidence: 68%
“…However, because of the low number of isolates (n512), it is not justifiable to say that there is high prevalence of fluconazole-resistant C. glabrata in this hospital. It is interesting to note that, despite the wide usage of fluconazole over the past decade, emergence of C. krusei infections due to selective pressure has not occurred, in contrast to the findings observed in other reports (Ruan et al, 2008). The MIC 90 values for itraconazole were highest for C. glabrata and C. parapsilosis.…”
Section: Discussioncontrasting
confidence: 55%
“…This observation is uncommon compared with almost all the previously reported studies that indicated some degree of sensitivity to amphotericin B. Although, in a study conducted by Ruan et al (2008), the resistance was extremely high against amphotericin B in C. krusei strains (95%) and in C. glabrata strains (53%), in recent years, the low rates of amphotericin B resistance have been reported in the C. albicans, C. glabrata, C. parapsilosis, C. tropicalis and C. krusei isolates (Metin et al, 2011;Taj-Aldeen et al, 2014).…”
Section: Discussioncontrasting
confidence: 42%